Evaluation of serum ESPL1 as a biomarker for early diagnosis of HBV-related hepatocellular carcinoma - Feng, Lu-Huai; Wei, Lu; Hu, Bobin; Liang, Hengkai; Li, Qingmei; Yin, Qianbing; Su, Tumei; Huang, Long; Liang, Hongqian; Jiang, Jianning; Su, Minghua (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the reliability of serum human phosphorylated exospindle polar-like proteinase 1 (ESPL1) as a serum biomarker for early diagnosis of hepatitis B virus (HBV)-related hepatocellular carcinoma (HBV-HCC).MethodsThis retrospective study was conducted on 266 patients with chronic hepatitis B (CHB), liver cirrhosis (LC), and HBV-related HCC. Data on demographics and clinical information were collected, and ESPL1 levels were measured using enzyme linked immunosorbent assay. Levels of ESPL1, alpha-fetoprotein (AFP), and protein induced by vitamin K absence -II (PIVKA-II) were compared at different disease stages, and spearman correlation analysis was used to assess their relationship with clinical markers. The diagnostic accuracy of ESPL1, AFP, and PIVKA-II for early HBV- HCC was assessed using ROC curve analysis.ResultsThe study comprised 121 patients diagnosed with CHB, 98 patients with LC, and 47 patients with HBV-HCC. Serum ESPL1 levels show an increasing trend across groups with chronic HBV infection, CHB, LC, and HBV-HCC, with levels at 224.6 ng/L, 285.8 ng/L, and 440.4 ng/L (in pairwise comparison, P<0.05). Serum AFP and PIVKA-II levels displayed no significant statistical differences between the CHB and LC groups. Spearman correlation analysis revealed that levels of ESPL1, PIVKA-II, and AFP are not influenced by clinical characteristics and show no correlation with each other. ROC curve analysis indicated that the optimal diagnostic threshold for ESPL1 in HBV-HCC is 345.7 ng/L, with AUC values for ESPL1, PIVKA-II, and AFP being 0.797 (95% CI: [0.708-0.886]), 0.788 (95% CI: [0.718-0.858]), and 0.572 (95% CI: [0.523-0.624]). In AFP and PIVKA-II negative patients, the AUC values for ESPL1 diagnosis of HBV-HCC were 0.79 and 0.83.ConclusionESPL1 is a potential biomarker for tracking chronic HBV infection and predicting the development of HBV-HCC. Monitoring ESPL1 levels in serum could help with early detection and personalized screening HBV-HCC for individuals with chronic HBV infection.